Approaching Laestadianism - Andreassen, Bengt-Ove; Kristiansen, Roald E.; Larsen, Rolf Inge (Approaching Religion, 2020)
The aim of this thematic issue on research on the Laestadian movement is to dwell with and look back on how the research on Laestadius and the Laestadian movement has developed, but at the same time show the latest developments in this research. In order to do so, researchers from the Nordic countries contributed to this thematic issue on research perspectives on the Laestadian movement. ‘Approaching Laestadianism’ presents theoretical articles and research overviews in order to present updates and tendencies in the research about the Laestadian movement.